Etika Penggunaan Teknologi Informasi dan Komunikasi dalam Perspektif Pendidikan Islam - Yan Fathur Rahman; Muhammad Naufal Aditya Perdana; Pauzan Haryono (CV. ITTC INDONESIA, 2026)
The development of Information and Communication Technology (ICT) has brought significant changes to the delivery of Islamic education, ranging from expanded access to learning resources and improved learning effectiveness to the growing use of Artificial Intelligence (AI) in teaching and learning processes. However, most prior studies have primarily focused on the technical aspects and effectiveness of digital learning media, while a comprehensive ethical framework aligned with Islamic values remains underexplored. This study aims to examine the development of ICT use, identify the ethical challenges associated with its implementation, and analyze the role of teachers' digital competence as a form of ethical ICT practice in Islamic education. A qualitative approach using the literature review method was employed, involving the search, screening, and synthesis of scholarly articles from databases such as Google Scholar, Scopus, Web of Science, ERIC, Dimensions, and Garuda, analyzed through thematic content analysis. The findings reveal that ICT integration, including AI, enhances accessibility, interactivity, and the professionalism of Islamic Religious Education teachers, yet simultaneously raises ethical concerns such as the misuse of personal data, algorithmic bias, diminished teacher-student interaction, and the potential erosion of the teacher's role as a moral guide (murabbi). From an Islamic perspective, technology must be positioned as a means (wasilah) rather than an end in itself, and its use must remain within the framework of maqāṣid al-sharī'ah, upholding the values of justice, trustworthiness, accountability, and privacy protection. Teachers' digital competence encompassing an integration of technological, pedagogical, and ethical competencies was identified as a key factor in the successful and ethical implementation of ICT. This study recommends the development of a comprehensive ethical model for ICT use grounded in Islamic values to serve as a policy and pedagogical guideline for Islamic educational institutions.